2013
DOI: 10.5296/ijl.v5i4.3794
|View full text |Cite
|
Sign up to set email alerts
|

How to Apply Critical Linguistics in English/Persian Literary Works’ Criticism

Abstract: Selecting the most appropriate technique of literary criticism as decoding approach of meaning clarification which best match various types of literary pieces has occupied the minds of literary critics in recent decades. Stylistics as an instrument for analyzing literary texts seems to grasp the critics' attentions and has proven itself as a powerful linguistic means of implicature derivation. This article attempted to depict how the knowledge of linguistic intricacies can affect the reader's interpretation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Oppression comes not simply with the obvious patriarchal structures; it can also come with the psychological and social formation of gendered subjects, who can be disabled as objects by controlling, dominant, but often unconscious, gendered interests (Kelly-Gadol, 1976).Analysis, therefore, is concerned with the construction and deconstruction of the political, social, psychological, and historical formations and processes of gendered text (see for example, Moi, 1985, Hadigheh & Khaghaninejad, 2013. Analysis is therefore about conflicting ideologies.…”
Section: Feminist Criticismmentioning
confidence: 99%
“…Oppression comes not simply with the obvious patriarchal structures; it can also come with the psychological and social formation of gendered subjects, who can be disabled as objects by controlling, dominant, but often unconscious, gendered interests (Kelly-Gadol, 1976).Analysis, therefore, is concerned with the construction and deconstruction of the political, social, psychological, and historical formations and processes of gendered text (see for example, Moi, 1985, Hadigheh & Khaghaninejad, 2013. Analysis is therefore about conflicting ideologies.…”
Section: Feminist Criticismmentioning
confidence: 99%
“…"However, in recent years, critical linguistics has also attracted the attention of the language community in my country. Indigenous research on critical discourse analysis has shown encouraging achievements [4]. The start of all computer language systems using statistical techniques today, this is because language and discourse are the same to some extent.…”
Section: Introductionmentioning
confidence: 99%